2006
DOI: 10.1007/s00464-005-0312-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-appraisal hierarchical task analysis of laparoscopic surgery performed by expert surgeons

Abstract: Surgeons' self-evaluation is accurate for technical skills aspects of their operations. This study demonstrates that self-appraisal using HTA is feasible, accurate, and practical. The authors aim to increase the numbers in their study and also to recruit residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 13 publications
1
31
1
1
Order By: Relevance
“…Consequently, a total of 12 papers were included (Table 3). 7,8,11,12,[16][17][18][19][20][21][22][23] According to our criteria, eight studies (66.7%) found that self-assessment of technical skills is accurate (Table 4). 11,[16][17][18][19][20][21][22] All studies were evidence level 2b.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Consequently, a total of 12 papers were included (Table 3). 7,8,11,12,[16][17][18][19][20][21][22][23] According to our criteria, eight studies (66.7%) found that self-assessment of technical skills is accurate (Table 4). 11,[16][17][18][19][20][21][22] All studies were evidence level 2b.…”
Section: Resultsmentioning
confidence: 92%
“…17 Increasing age and non-European nationality were found to increase self-assessment accuracy in one study (8.3%) 22 (level 3 recommendation). One study 18 A variety of technical skills were assessed. Four studies (33.3%) assessed multiple surgical skills.…”
Section: Participants Undertaking the Self-assessment Processmentioning
confidence: 99%
See 3 more Smart Citations